FAN-DRIVEN MARKETING COMMUNICATION: IMPLEMENTATION OF THE SOSTAC® MODEL IN PROMOTING SALMA SALSABIL’S SONG “BUNGA HATI” BY SALMINE FANBASE (Proceeding of SINERGY, 2026)
In today’s digital landscape, fanbases play a crucial role in boosting their idols' popularity. This study examines the marketing communication strategies employed by the Salmine fan base to promote Salma Salsabil’s song “Bunga Hati” on social media, utilizing the SOSTAC model. Using a qualitative approach, data were gathered through observation, interviews, and documentation, then analyzed using the Miles and Huberman technique. The results indicate that the song’s promotional success was significantly influenced by the active participation of Salmine Creators and Salmastreams, two fanbase divisions responsible for content strategy and streaming optimization. The fanbase employed multiple strategies, such as creative content production, digital campaigns, and streaming optimization, to increase the song’s exposure. Moreover, capitalizing on social media trends, collaborating with key opinion leaders, and implementing digital word-of-mouth strategies played a key role in amplifying its reach. With a well-structured promotional system, “Bunga Hati” successfully climbed music charts and received prestigious awards. These findings highlight that fanbase-driven marketing on social media is a powerful and effective strategy within the digital music industry.